Arithmetic Progression II

123 , 103 , 83 , 63... 123, 103, 83, 63...

In the AP above, find the 86th term.

-1577 -1566 -1555 -1544

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Mardokay Mosazghi
Apr 22, 2014

First observe the arithmetic proggresion. 123 , 103.. 123,103.. continues by subtracting 20 20 so the common difference is -20, the first term is |(123) so the equation is n + ( n 1 ) d n+(n-1)d in which d= difference between numbers so 123 + ( 86 1 ) × 20 123+(86-1)\times -20 so now 123 + ( 85 ) 20 123+(85)*-20 123 + ( 1700 ) 123+(-1700) so the answer is 1577 \boxed{-1577}

Exactly

Aaditya Pratap - 7 years, 1 month ago

Nice soluction...

Heder Oliveira Dias - 6 years, 11 months ago

yes absolutely right

reshma ramesh - 6 years, 11 months ago
Vishal S
Dec 22, 2014

In A.P nth term is given by

n=a+(n-1)d

here n=86, a=123 & d=-20

=> n=123+(85)(-20)

=>n=-1577

therefore 86th term is -1577

a=123; d=-20; n=86. Thus a_{n} = a+(n-1)d = 123+(85)(-20) = 123 -1700 =-1577

Awik Try
Jun 5, 2014

easy way, the concept of sequence numbers with each - each different from 20. 123,103,83,63,43,23,3, ..... and so on by using the results of using the multiplication factor 3, ie 27, see the end of 7 that its contents

The formula used is:- tn = a + ( n - 1 ) * difference

Where tn = term number , a = first number of the sequence

In this sequence the numbers are in decreasing order. So, instead of difference 20 we should use -20.

Tn = a + ( n - 1 ) * difference

= 123 - 20n + 20

= -20n + 143

So we got the formula and have to find the 86th term.

= -20n + 143

= ( -20 * 86 ) + 143

= -1720 + 143

= -1577

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...